ECTHR_CHAMBER 32006/20 vom 14. Dezember 2021 , AFFAIRE D.I. c. BULGARIE - Ecthr Chamber (2021)
Non-violation de l'article 3 - Interdiction de la torture (Article 3 - Extradition) (Conditionnel); No violation: 3